ANALISIS IMPROVE MAKLON PADA PRODUKSI KRIMER DENGAN PENDEKATAN QUALITY FUNCTION DEPLOYMENT DI PT X - Widjaya, Christian Chandra; Walujo, Djoko (University of Riau Kepulauan, 2024)
Packaging is an important part of the product. Packaging is not only to protect the product from danger and contamination of the product itself. But packaging is also used to attract the attention of consumers. PT X is one of the manufacturing companies in the food and beverage sector, where PT X also produces products in maklon packaging. Several companies similar to PT X, also produce in maklon packaging, which makes competition in the market even tighter. The purpose of this research is to produce improved packaging for PT X creamer products with the Quality Function Deployment approach. The tests carried out this time are very important for the basis for making changes by looking at the level of aspects needed by consumers from 30 respondents. the results of research that have been carried out using the Quality Function Deployment method there are several attribute values in the level of their improvement ratio in development by determining the attribute values that respondents have chosen in development. For the attribute itself on ‘Simple Minimalist Design’ which has a high level of importance with an improvement ratio value of 1.21.